A Three‐Dimensional Dynamic Supramolecular "Sticky Fingers" Organic Framework. Issue 8 (24th January 2019) - Fernandez‐Bartolome, Estefania; Santos, José; Gamonal, Arturo; Khodabakhshi, Saeed; McCormick, Laura J.; Teat, Simon J.; Sañudo, E. Carolina; Costa, José Sánchez; Martín, Nazario
Abstract: Engineering high‐recognition host–guest materials is a burgeoning area in basic and applied research. The challenge of exploring novel porous materials with advanced functionalities prompted us to develop dynamic crystalline structures promoted by soft interactions. The first example of a pure molecular dynamic crystalline framework is demonstrated, which is held together by means of weak "sticky fingers" van der Waals interactions. The presented organic‐fullerene‐based material exhibits a non‐porous dynamic crystalline structure capable of undergoing single‐crystal‐to‐single‐crystal reactions. Exposure to hydrazine vapors induces structural and chemical changes that manifest as toposelective hydrogenation of alternating rings on the surface of the [60]fullerene. Control experiments confirm that the same reaction does not occur when performed in solution. Easy‐to‐detect changes in the macroscopic properties of the sample suggest utility as molecular sensors or energy‐storage materials. Abstract : A sticky situation : An unprecedented pure, dynamic, crystalline framework held together with weak "sticky fingers" van der Waals interactions has been developed. The fullerene‐based material exhibits a remarkable single‐crystal‐to‐single‐crystal hydrogenation reaction accompanied by a color change in the visible range.